An extension of commonly used toilet‐training procedures to children with autism spectrum disorder. Issue 4 (26th May 2020) - Perez, Brandon C.; Bacotti, Janelle K.; Peters, Kerri P.; Vollmer, Timothy R.
Abstract : The current study evaluated a toilet‐training treatment package described by Greer et al. (2016) with children diagnosed with autism spectrum disorder (ASD). Most of the current research on toilet‐training interventions for children with ASD are replications and modifications of Azrin and Foxx (1971) or (more recently) LeBlanc et al. (2005). However, these procedures are composed of components that are not included in studies with typically developing (TD) children. For example, Greer et al. evaluated the effectiveness of three typical components within a toilet‐training package, mostly with TD participants: a 30‐min sit schedule, placing participants in underwear, and differential reinforcement. The primary purpose of the current study was to replicate and extend the treatment package described by Greer et al. to children with ASD. A secondary purpose was to evaluate modifications necessary for individualized toilet training when the commonly used components were ineffective. The results of Greer et al. were replicated for 11 participants with ASD in the current study, suggesting that intensive toileting interventions (e.g., interventions requiring overcorrection, reprimands, and dense sit schedules) may only be necessary for a subset of individuals with ASD.